1989
DOI: 10.1002/micr.1920100108
|View full text |Cite
|
Sign up to set email alerts
|

Strength of microvascular anastomoses: Comparison between the unilink anastomotic system and sutures

Abstract: The Unilink system, a mechanical anastomotic device, was compared with standard suture techniques in terms of anastomotic strength under conditions of uniaxial loading. Twenty-five rabbits underwent Unilink and suture anastomosis of both carotid arteries and facial veins. Animals were sacrificed at 1 hour (five animals), 2 weeks (10 animals), and 16 weeks (10 animals), and all vessels were tested by constant loading in a material testing machine. The maximum load required to disrupt the anastomosis as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…One example is the microvascular anastomotic coupling device (MACD), an interlocking ring-pin design that is becoming more widely used in FTT. Initial animal studies demonstrated favourable tensile characteristics and healing of coupled vessels (3), and subsequent case series in head and neck, breast and limb reconstructive surgery have reported favourably on MACD utilization. These case series have been limited by smaller numbers and variability in reconstructive subsites; however, recently, several larger series have been published.…”
mentioning
confidence: 99%
“…One example is the microvascular anastomotic coupling device (MACD), an interlocking ring-pin design that is becoming more widely used in FTT. Initial animal studies demonstrated favourable tensile characteristics and healing of coupled vessels (3), and subsequent case series in head and neck, breast and limb reconstructive surgery have reported favourably on MACD utilization. These case series have been limited by smaller numbers and variability in reconstructive subsites; however, recently, several larger series have been published.…”
mentioning
confidence: 99%
“…Among the components of this device are gauges for measuring the vessel diameter for appropriate matching of the size of the ring in order to avoid stenosis. Scanning electron microscopy of ringed anastomoses has shown smooth and complete endothelial healing in both arterial and venous anastomoses after 2 weeks 20 and, while marked atrophy of the media at the site of the anastomotic rings was observed, this did not seem to affect the patency rate, which compared favourably with that of sutured controls 17,19,22,102,103 . The Unilink system  fits with Carrel's third and fourth principles, alignment of both intimal layers and absence of intraluminal foreign material.…”
Section: Discussionmentioning
confidence: 56%
“…8,11,[13][14][15][16][17][18][20][21][22][23][24]34 Anastomotic strength has been tested in animal models and found to generally exceed that of traditional anastomoses. 35 One of the inherent benefits of anastomoses created using coupling devices is the absence of any intraluminal foreign material, which might be a nidus for thrombus formation. Critics of the coupler suggest that because of the penetrative nature of the device, the thrombogenic subendothelial collagen matrix may become exposed.…”
Section: Couplermentioning
confidence: 99%